Therapeutic efficiency of trimetazide MR in patients with type 2 diabetes mellitus after myocardial infarction - E E Novitskaya; G A Baryshnikova (Сахарный диабет)
Aim. To evaluate efficiency of trimetazide MR combined with basic therapy of type 2 diabetes mellitus (DM2) in patients with myocardial infarction (MI). Materials and methods. The study included 106 patients with DM2 who underwent MI. Polycomponent basic therapy supplemented by trimetazideMR at a daily dose of 70 mg was given to 51 patients. The patients condition 6 and 12 months after treatment was evaluated from the results of echo-CG, 24 hr ECG monitoring, and 6 min walking test. Quality of life was estimated using modified Minnesota questionnaire scores. Results. Trimetazide MR combined with polycomponent basic therapy reduced consumption of nitroglycerine by DM2 patients after myocardial infarction,frequency of ventricular and supraventricular extrasystole in 25.3 and 25.3% of the cases respectively. Episodes of painless myocardial ischemiaoccurred only in 35.6% of the patients. Long-term treatment with trimetazide MR as a component of combined therapy increased injectionfraction in patients with abnormal myocardial contractility (p